2001
DOI: 10.1038/sj.ijo.0801511
|View full text |Cite
|
Sign up to set email alerts
|

Does the BMI reflect body fat in obese children and adolescents? A study using the TOBEC method

Abstract: OBJECTIVE: Due to the fact that obesity is de®ned as excess of body fat mass, we tested the hypothesis whether the body mass index (BMI) can be used as a valid measure for the detection of the degree of obesity in individual obese children and adolescents. METHODS: A total of 204 obese children and adolescents (105 boys, 99 girls) aged 6 ± 17 y, using total body electrical conductivity (TOBEC) for fat measurement, were included into this study.A multiple regression analysis was performed with percentage body f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
0
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 22 publications
4
38
0
5
Order By: Relevance
“…[8][9][10][11][12][13][14][15][16][17][18][19][20][21] For example, BMI was strongly associated with %body fat (r ¼ 0.83-0.94) among Pima Indian children (whose mean BMI was B5 kg/ m 2 higher than participants in the current study), 16 whereas a correlation of r ¼ 0.46 was observed among adolescent girls with anorexia nervosa (mean BMI ¼ 13.5 kg/m 2 ). 21 In agreement with the sex and age differences in body fatness, it has also been reported that the associations with BMI are stronger among females than among males, 4,10,11 and among 7-to 10-y-old boys than among 14-to 16-y-old boys.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…[8][9][10][11][12][13][14][15][16][17][18][19][20][21] For example, BMI was strongly associated with %body fat (r ¼ 0.83-0.94) among Pima Indian children (whose mean BMI was B5 kg/ m 2 higher than participants in the current study), 16 whereas a correlation of r ¼ 0.46 was observed among adolescent girls with anorexia nervosa (mean BMI ¼ 13.5 kg/m 2 ). 21 In agreement with the sex and age differences in body fatness, it has also been reported that the associations with BMI are stronger among females than among males, 4,10,11 and among 7-to 10-y-old boys than among 14-to 16-y-old boys.…”
Section: Discussionmentioning
confidence: 73%
“…BMI levels among adults are highly correlated with %body fat, and in combination with race, sex, and age, multiple R 2 -values of 0.7-0.8 have been reported. [4][5][6][7] Associations among children and adolescents have been more variable, [8][9][10][11][12][13][14][15][16][17][18][19][20][21] and relatively weak correlations (ro0.6) have been reported in several subgroups. 8,10,11,13,15,21 These weaker associations among children and adolescents may be attributable to the asynchronous changes that occur in the levels of fat mass and fat-free mass during growth.…”
Section: Introductionmentioning
confidence: 99%
“…BF% correlates well with BMI in children aged 6-9 years but exhibits a reduced degree of correlation with BMI in adolescents, in boys and at the extremes of BMI (15) . To date, only a handful of studies have investigated the nature of the association of both adiposity indices (BMI and BF%) with vitamin D in healthy adolescents across the whole spectrum of adiposity, with some however not adjusting for the effect of potential confounders (5,6,9) .…”
mentioning
confidence: 84%
“…Alternatively, body mass index (BMI) (weight/height 2 ) is a valid and reproducible method that is cheap and convenient for the assessment of weight status (where weight becomes a surrogate for body fatness) in epidemiological studies. BMI is commonly used in adults and more recently recommended for use in children and adolescents (Power et al, 1997;Bellizzi and Dietz, 1999;Dietz and Bellizzi, 1999;Bini et al, 2000;Reilly et al, 2000;Widhalm et al, 2001). However, the assessment of weight status in young people is more complex, when using BMI to assess adiposity in children and adolescents it is essential that age-and sex-specific BMI cutoffs be used to define overweight and obesity (Widhalm et al, 2001;Field et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…BMI is commonly used in adults and more recently recommended for use in children and adolescents (Power et al, 1997;Bellizzi and Dietz, 1999;Dietz and Bellizzi, 1999;Bini et al, 2000;Reilly et al, 2000;Widhalm et al, 2001). However, the assessment of weight status in young people is more complex, when using BMI to assess adiposity in children and adolescents it is essential that age-and sex-specific BMI cutoffs be used to define overweight and obesity (Widhalm et al, 2001;Field et al, 2003). Given the economic, environmental, genetic and nutrition influences on body size, having growth standards that are nationally representative is an important consideration (Livingstone, 2000).…”
Section: Introductionmentioning
confidence: 99%